Мовні права як категорія соціолінгвістики - Ажнюк, Б.М. (Мовознавство, 2013)
У статті подано характеристику категорії «мовні прав», що ґрунтується на дослідженні актів мовного законодавства ряду країн, а також актів міжнародного права. На думку автора, мовні права не обмежуються тільки мовними меншинами, а повинні враховувати також інтереси і прагнення мовної спільноти, що представляє титульну надію. Захист мовних прав у багатомовному соціумі передбачає збалансований підхід до мовних потреб і законних інтересів мовної більшості і мовних меншин. The discussion on language rights is affected by the lack of clarity about the scope and structure of this linguistic category, its nature and status and the differences of approaches to the protection of language human rights. In this paper a characteristics of language rights based upon the study of national legislations of a number of countries as well as the international legal documents is proposed. It is argued that language rights are not limited only to the linguistic minorities and have to be also considered in the context of the interests and aspirations of the host language community. The protection of language human rights in a multilingual environment presupposes a balanced approach to the language majority and language minorities concerns and legitimate needs. The impact of the terms denoting language status on the treatment of linguistic rights in language legislation is discussed. The point being made in this paper is that recognition of language rights is based on historical and hereditary reasons and it bares considerable influence on the language substance: the vocabulary, grammar, orthography etc.